The structure–property relationships of acid- and alkali-extracted grapefruit peel pectins. (1st February 2020) - Cui, Jiefen; Ren, Wenbo; Zhao, Chengying; Gao, Wei; Tian, Guifang; Bao, Yuming; Lian, Yunhe; Zheng, Jinkai
Highlights: Grapefruit peel pectins extracted by acid and alkali were systematically compared. The cross-linked network nanostructure of P10 and P11 was characterized by AFM. The effect of acid/alkali extraction on pectin conformation was studied by SAXS. Relationship between pectin conformation and functional properties was analyzed. Abstract: Structure and properties of pectin can be affected by extraction methods. In this study, grapefruit peel pectins extracted by HCl (at pH 1 [P1], 2 [P2], and 3 [P3]) and NaOH (at pH 9 [P9], 10 [P10], and 11 [P11]) were prepared and characterized. Atomic force microscopy (AFM) provided direct evidence of complex nano-structural patterns of pectins and revealed cross-linked networks of P10 and P11. Small-angle X-ray scattering (SAXS) demonstrated that P1, P2, and P3 possessed a relatively extended conformation, whereas P9, P10, and P11 displayed a three-dimensional structure and folded conformation. The compact and extended conformations of P3 contributed to its high viscosity in solution and the stability of the formed emulsion (75%). Porous surface and larger three-dimensional nanostructure (Dmax : 23 nm) of P10 facilitated its ion-binding capacity. Our results provide valuable insight into relationship between extraction methods and structure-properties of pectin, facilitating design of functional pectins.